2021
DOI: 10.1017/s000712342100051x
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Citizens? Ideological Structure and Conflict Extension in the US Electorate, 1980–2016

Abstract: Past the half-century mark of Converse's (1964) field-defining essay, the nature of political ideology in the mass public and how it has changed in response to partisan polarization remains enigmatic. To test the ideological structure of US public opinion, I develop and implement a Bayesian dynamic ordinal item response theory model. In contrast to static scaling procedures, this method allows for changes in the mappings between issue attitudes and the underlying ideological dimension over time. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…We refer to the first type of individuals as Downsians because of their relationship to the voters described in Downs (1957). These individuals have preferences across policy questions that are well approximated by an ideal point on an underlying liberal–conservative ideological dimension (e.g., Bafumi and Herron 2010; Hare 2021; Jessee 2012; Tausanovitch and Warshaw 2013). We anticipate that there will be many liberal and conservative Downsians.…”
Section: Data and Measurement Modelmentioning
confidence: 99%
“…We refer to the first type of individuals as Downsians because of their relationship to the voters described in Downs (1957). These individuals have preferences across policy questions that are well approximated by an ideal point on an underlying liberal–conservative ideological dimension (e.g., Bafumi and Herron 2010; Hare 2021; Jessee 2012; Tausanovitch and Warshaw 2013). We anticipate that there will be many liberal and conservative Downsians.…”
Section: Data and Measurement Modelmentioning
confidence: 99%
“…Current research indicates that partisan animosity is rooted in substantive disagreements (Orr and Huber 2020;Dias and Lelkes 2022). Ideological conflict represents a significant discrepancy between comprehensive narratives, leading to extended troubling conflicts (Layman and Carsey 2002;Hare 2022).…”
Section: Ideological Alignment Among Partisansmentioning
confidence: 99%
“…For instance, the ideological rifts in the US public have deepened, making it challenging to bridge or reconcile the two comprehensive albeit radically opposing narratives (Levendusky 2010b;Mason 2015;Abramowitz 2022;Hare 2022). A troubling consequence of this rise in ideological alignment is the increasing animosity between different partisan camps, known as affective polarization (Homola et al 2023).…”
mentioning
confidence: 99%
“…social and economic), and social ideas and policies have ramifications for the economic domain and vice versa. Recently, Hare (2022) demonstrated that the social and economic dimensions of ideology in the US have become increasingly intertwined over the past four decades and that opinions on policy controversies about economic, social and racial issues better fit a unidimensional ideological structure in the US. Similarly, Stoetzer and Zittlau (2020) found that in US presidential elections, voters' attitudes about social and economic policies have become almost non‐separable and collapse into a single dimension.…”
Section: Introductionmentioning
confidence: 99%